(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
Love and hate are a duality that can depict either opposite identities or differences growing from a common ground. This paper, following Nietzsche, explores the latter position as shown by Dionysos in the Bacchae. He introduced wine to mankind and is the god of the theatre. He dissolves and transcends boundaries and so destroys those who are fixated on any identity. He is the ecstatic god.